Signifikansi Studi Kitab Wahyu dalam Kehidupan Bergereja - Jefri Andri Saputra (Sabda: Jurnal Teologi Kristen, 2022)
The book of Revelation is the most difficult part to study or interpret of all the books in the Bible. This difficulty makes this book “difficult” to function as the word of God. This condition encourages the writer to examine the book of Revelation and its benefits for the life of the congregation. Using a qualitative descriptive approach, the author examines various literatures to discuss the genre, background and method of interpreting the book of Revelation. At the end of this paper, the author finds that the book of Revelation is an important book to help the church respond to various challenges both from within and from outside the church.